The legal regulation of artificial intelligence technologies - AbuMalik, Talal Hussein; AL Saidat, Enad Atieh Oqla; El-Shqeirat, Faisal Mohammad; Smairan, Abdalelah Mohammed; Bader, Majdoleen Rasmi Kamel; Al-Naimat, Osamah (Research Journal in Advanced Humanities, 2026)
This study, entitled The Legal Regulation of Artificial Intelligence Technologies, addresses several legal issues raised by artificial intelligence technologies, particularly those related to determining the nature of civil legal protection afforded to such technologies. This necessitated an examination of the mechanisms and methods by which the Jordanian legislator has sought to incorporate artificial intelligence technologies into existing legal texts. The study reached several conclusions, most notably that the definition of the “electronic agent” as provided by the Jordanian legislator in Article (2) of the Electronic Transactions Law of 2015 may encompass, in its substance, the concept of artificial intelligence (AI). However, this definition is limited to certain characteristics of these technologies, such as inference and autonomy in transmission, while overlooking other essential features, including their ability to learn, make decisions independently without human intervention, and possess deductive reasoning capabilities. Accordingly, the study recommends amending the definition of the electronic agent contained in the Electronic Transactions Law of 2015 to encompass all the characteristics inherent in artificial intelligence technologies, such as deduction, self-learning, and independent decision-making without human intervention.